2002
DOI: 10.2131/jts.27.19
|View full text |Cite
|
Sign up to set email alerts
|

Effects of perinatal exposure to flutamide on sex hormones and androgen-dependent organs in F1 male rats.

Abstract: Flutamide, which has antiandrogenic properties, was administered to pregnant rats, and effects on male offspring were examined. Crj: CD (SD) IGS (SPF) females were administered flutamide (0.15, 0.6, 2.5, 10.0, 100 mg/kg, p.o.) from gestation Day 14 to post parturition Day 3. The number of pups, body weights, clinical features, anogenital distance (AGD), nipple retention, testicular descent, and urogenital malformation in F1 males were examined. Hormone measurement, necropsy and histopathological examination we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
55
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(63 citation statements)
references
References 46 publications
5
55
0
Order By: Relevance
“…Miyata et al (2002) reported that oral administration of flutamide at ≥ 2.5 mg/kg/day from GD 14 to PND 3 decreased AGD, and McIntyre et al (2001) observed similar findings at oral doses of 6.25 mg/kg/day. In our study too, decreased AGD was induced from low dose while abnormalities of the internal genitalia (e.g., prostate hypoplasia) occurred at 10 mg/kg and higher.…”
Section: Discussionmentioning
confidence: 67%
See 3 more Smart Citations
“…Miyata et al (2002) reported that oral administration of flutamide at ≥ 2.5 mg/kg/day from GD 14 to PND 3 decreased AGD, and McIntyre et al (2001) observed similar findings at oral doses of 6.25 mg/kg/day. In our study too, decreased AGD was induced from low dose while abnormalities of the internal genitalia (e.g., prostate hypoplasia) occurred at 10 mg/kg and higher.…”
Section: Discussionmentioning
confidence: 67%
“…ers have reported similar effects of flutamide (Miyata et al, 2002;McIntyre et al, 2001) and other antiandrogen agents (Shono et al, 2004;Barlow et al, 2004;Ema et al, 2003;Bowman et al, 2003) on sexual maturity in males. Miyata et al (2002) reported that oral administration of flutamide at ≥ 2.5 mg/kg/day from GD 14 to PND 3 decreased AGD, and McIntyre et al (2001) observed similar findings at oral doses of 6.25 mg/kg/day.…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…We elected to attempt to alter the differentiation of the epididymis with flutamide, a potent non-steroidal antiandrogen [9] that competes for the androgen receptor and is capable of reducing the physiological action of testosterone on target tissues when endogenous tissue levels of androgen are submaximal [10,11]. Between PND 21 and 44 androgen levels in the epididymis are on the rise, but far less than adult levels [8].…”
Section: Introductionmentioning
confidence: 99%